2013
DOI: 10.1136/emermed-2011-200407
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of the increasing prevalence of the poisonousLagocephalus sceleratusin southern Turkey

Abstract: General health organisations are unprepared for the serious health hazards caused by this fish, including fatalities. Health workers should have sufficient knowledge regarding the clinical manifestations, complications and management of puffer fish poisoning. Official authorities should make the public aware of the potential risk of consuming puffer fish.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 10 publications
0
22
0
Order By: Relevance
“…Consumption of these species can result in human fatalities (Beköz et al, 2013), and this study highlights that Turkish fishers do not have enough information about the poisonous status of pufferfish. The consumption rate is higher in commercial fishers than recreational fishers.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Consumption of these species can result in human fatalities (Beköz et al, 2013), and this study highlights that Turkish fishers do not have enough information about the poisonous status of pufferfish. The consumption rate is higher in commercial fishers than recreational fishers.…”
Section: Discussionmentioning
confidence: 87%
“…Moreover, these species reduce the local stocks of commercial species through the predation (Kalogirou, 2013). Some Lessepsians, such as pufferfish are also dangerous for human and animal consumption (Chamandi et al, 2009;Beköz et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…This fish is also present in Turkey and Greece [43,44]. Since its recent introduction, Lagocephalus sceleratus has already invaded the Eastern half of the Mediterranean (with proven presence in Tunisia [45] and Libya [46]) and its arrival in the western Mediterranean seems imminent [47]. It should be noted that an equally toxic indigenous pufferfish species Lagocephalus lagocephalus is sporadically observed along the North African Mediterranean coast from Morocco to Libya but this pelagic species from the Atlantic is rarely caught.…”
Section: Lessepsian and Invasive Fish Speciesmentioning
confidence: 99%
“…According to the current European Union (Regulation 853/2004/EC; Regulation 854/2004/EC) and Turkish legislative requirements (Anonymous, 2012), poisonous fish of the family Tetraodontidae and products derived from them must not be placed on the markets. However, probably due to its large size that can reach up to 110 cm and weight up to 7 kg (Froese & Pauly, 2014), it is being sold and consumed in some Mediterranean countries like Egypt, Israel, Turkey and Lebanon and there are several cases of poisoning (Aydın, 2011;Nader, Indary, & Boustany, 2012;Beköz, Beköz, Yılmaz, Tüzün, & Beköz, 2013). In addition to its great risk to human health if consumed, L. sceleratus has been recorded to destroy fishing nets and lines by its two strong teeth in each jaw, leading to economic losses for fishers (EastMed, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Due to its rapid expansion and potential threats to humans, L. sceleratus was the subject of several recent studies in Turkey with different aspects (Aydın, 2011;Başusta, Başusta, & Özer, 2013;Beköz et al, 2013;Köşker, Özoğul, Ayas, Durmuş, & Uçar, 2015). Previously a few studies have also reported the (Gücü, 2012;Yemişken, Dalyan, & Eryılmaz, 2014;Bilecenoğlu, 2016).…”
Section: Introductionmentioning
confidence: 99%